Comparative genomic analysis of resistance and virulence genes in staphylococcus epidermidis and their impact on clinical outcome of musculoskeletal infections - Ingrid Nayara Marcelino Santos; Felipe Alberto-Lei; Fernanda Fernandes Santos; Mariana Felix Cerqueira Balera; Mariana Neri Kurihara; Carolina Coelho Cunha; Laís Sales Seriacopi; Thomas Stravinskas Durigon; Fernando Baldy Reis; Ana Karolina Antunes Eisen; Giovana Santos Caleiro; Jansen de Araújo; et al. (Scientific Reports)
Abstract Staphylococcus epidermidis is an opportunistic commensal cutaneous biofilm-producing agent frequently causing musculoskeletal infections (MSI) with/without implants. This study was design to evaluate phenotypic and genomic relatedness between commensal skin and MSI S. epidermidis isolates and to assess patient-related and microbial markers in the outcome of patients after one-year follow-up. Demographics, clinical data and monomicrobial S. epidermidis isolates of MSI patients (n = 31) and healthy individuals (n = 15) were analyzed. Phenotypic profile was assessed by susceptibility tests by broth microdilution and biofilm formation. Phylogenetic relationships, resistome characterization, and virulome analysis were carried out by complete genome sequencing (n = 46). Overall, MSI-derived isolates were significantly more strong/moderate biofilm producers and depicted higher rates of resistance to methicillin (MRSE), ciprofloxacin, gentamicin and rifampicin. Demographics and clinical characteristics did not significantly affect MSI patients’ outcomes. In the whole-genomic sequencing (WGS) phylogeny, most MSI-derived isolates were grouped into the pathogenic-associated clonal complex CC2, and significantly higher prevalence of mecA gene and pathogenic marker IS256. Following multivariate analysis, MSI-derived isolates carrying transposable element IS256 are more likely to develop a persistent infection (odds ratio [OR], 8.00, [95% confidence interval (CI), 1.06 to 60.31], P = 0.044), while weaker biofilm producer were protectors (OR, 0.070, 95%CI, 0.005–0.979, P = 0.048), reducing the chance of recurrence by 93% (1–0.070). The logistic regression model’s performance was evaluated by Nagelkerke’s R, which resulted in 47.21%. In conclusion, S. epidermidis isolates producing MSI were phenotypically and genetically distinct from commensals, proven the association between independent genetic traits and patient’s outcome.